Computer concepts - Shepherd, Robert D. (EMC Paradigm, 1997)
COMPUTER Concepts is Paradigm's textbook for introduction to computers courses. With this text students will learn the computer skills they need to succeed in their academic and professional lives. The text provides comprehensive coverage of computer concepts-including hardware, software, the Internet, social media, security, and ethics. Challenging end-of-chapter exercises move students from simple recall to advanced thinking and analysis of IT issues.